2016
DOI: 10.1016/j.addbeh.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of implicit and explicit drinking identity in a large US adult sample

Abstract: Drinking identity (viewing oneself as a drinker) is a potential risk factor for problematic drinking in US undergraduate samples. Whether that risk extends to a broader, more general US sample is unknown. Additionally, there are critical, unanswered questions with respect to moderators of the drinking identity–problematic drinking relationship; an important issue for designing prevention efforts. Study aims were to assess the unique associations and interactive effects of implicit and explicit measures of drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 28 publications
3
25
3
Order By: Relevance
“…Explicit measures of alcohol self-concept have been added to prominent theoretical models of drinking (e.g., the Theory of Planned Behavior) and have been found to improve them (45). Recent studies have examined moderators of the relationship between explicit alcohol self-concept and drinking outcomes and have demonstrated that explicit alcohol self-concept is a stronger predictor of drinking outcomes among younger individuals (46) as well as in individuals high in individualism (47), high in levels of self-control (48), and low in motivation to reduce their drinking (49). Finally, explicit alcohol self-concept appears to mediate the positive relationship between drinking motives and alcohol consumption (49).…”
Section: Implicit and Explicit Measures Of Substance Self-concept: Fimentioning
confidence: 99%
See 3 more Smart Citations
“…Explicit measures of alcohol self-concept have been added to prominent theoretical models of drinking (e.g., the Theory of Planned Behavior) and have been found to improve them (45). Recent studies have examined moderators of the relationship between explicit alcohol self-concept and drinking outcomes and have demonstrated that explicit alcohol self-concept is a stronger predictor of drinking outcomes among younger individuals (46) as well as in individuals high in individualism (47), high in levels of self-control (48), and low in motivation to reduce their drinking (49). Finally, explicit alcohol self-concept appears to mediate the positive relationship between drinking motives and alcohol consumption (49).…”
Section: Implicit and Explicit Measures Of Substance Self-concept: Fimentioning
confidence: 99%
“…Both IATs have good psychometrics and predict unique variance in multiple alcohol-related outcomes among college student and adult samples, including self-report and lab-based alcohol consumption, problems, harm, cravings, and behavioral economic indices of alcohol demand (9,20,41,46,5053). The Drinker Identity IAT also predicted unique variance in drinking after controlling for explicit alcohol self-concept, other well-validated alcohol-related IATs (9,20,39), and other well-validated cognitive factors (e.g., alcohol expectancies, drinking motives, social norms) associated with drinking outcomes (40).…”
Section: Implicit and Explicit Measures Of Substance Self-concept: Fimentioning
confidence: 99%
See 2 more Smart Citations
“…These deficits could have implications for understanding how hazardous drinking may be differentially associated with implicit/explicit drinking identity. Specifically, conscious self-awareness is believed to be necessary for the measurement of explicit, but not necessarily implicit, drinking identity (Lindgren, Gasser, et al, 2016). Thus, at low levels of hazardous drinking, when there would presumably be few to no deficits in self-awareness, implicit and explicit drinking identity would become stronger as hazardous drinking increases.…”
Section: Introductionmentioning
confidence: 99%